TRPA1‐mediated responses in trigeminal sensory neurons: interaction between TRPA1 and TRPV1 - Margaux M. Salas; Kenneth Hargreaves; Armen N. Akopian (2009)
Abstract The transient receptor potential (TRP)A1 channel is involved in the transduction of inflammation‐induced noxious stimuli from the periphery. Previous studies have characterized the properties of TRPA1 in heterologous expression systems. However, there is little information on the properties of TRPA1‐mediated currents in sensory neurons. A capsaicin‐sensitive subset of rat and mouse trigeminal ganglion sensory neurons was activated with TRPA1‐specific agonists, mustard oil and the cannabinoid WIN55,212. Mustard oil‐ and WIN55,212‐gated currents exhibited marked variability in their kinetics of activation and acute desensitization. TRPA1‐mediated responses in neurons also possess a characteristic voltage dependency with profound outward rectification that is influenced by extracellular Ca 2+ and the type and concentration of TRPA1‐specific agonists. Examination of TRPA1‐mediated responses in TRPA1‐containing cells indicated that the features of neuronal TRPA1 are not duplicated in cells expressing only TRPA1 and, instead, can be restored only when TRPA1 and TRPV1 channels are coexpressed. In summary, our results suggest that TRPA1‐mediated responses in sensory neurons have distinct characteristics that can be accounted for by the coexpression of the TRPV1 and TRPA1 channels.